SARKASME DALM LIRIK LAGU ALBUM MEMBANGUN DAN MENGHANCURKAN KARYA BAND .FEAST - Raesmawati, Resti; Aditya Damayanti, Deasy; Asmaniah, Zainah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study analyzes the use of sarcasm in the lyrics of six songs from the album Membangun dan Menghancurkan (2024) by the band .Feast, namely "Membangun", "Konsekumens", "Masimarah", "Arteri", "Tarot", and "5", with a total of 26 sarcastic lyric quotes. Using Aminuddin's (1995) stylistic approach combined with Gorys Keraf's (2009) classification of sarcasm as a sharp satirical figurative language style, it was found that the functions were spread out into emotive (11 lyrics, for example: "Your badness is displayed openly" expressing anger), persuasive (4, for example: "In the air your sins are completely recorded" persuading digital awareness), symbolic (8, for example: "I build God myself" symbol of personal values), and social criticism (7, for example: "The five-year cycle of building and destroying" repeated political mockery), while the meaning was dominated by social criticism (11, for example: "Forced to be proud and love the country, cursed to finance the minister's house" mocking forced nationalism), symbolic (10), emotive (6), and persuasive (3), with some overlap and multiple functions. This album reflects a shift from the social criticism of the previous album to a personal theme of self-transformation, although it remains critical of political hypocracy, urban inequality, and social media ethics in contemporary Indonesia. The descriptive qualitative method involves data collection from original lyrics, analysis of implicit meanings, and aesthetic effects, showing sarcasm as an effective tool for emotional expression, provocation of reflection, and subtle satire that enrich the stylistics of local pop-rock music. This research is relevant for literary education to integrate song lyrics as teaching materials for stylistic analysis, encouraging listeners' critical awareness of social reality.